Firm Heterogeneity, Industry Characteristics and Types of FDI: The Case of German FDI in the Czech Republic - Holger Görg; Henning Mühlen; Peter Nunnenkamp (Aussenwirtschaft, 2010)
In addition to firm and industry characteristics, the heterogeneity of foreign direct investment (FDI) has to be taken into account when analyzing the determinants of outward FDI. We combine two firm-specific datasets on German firms with subsidiaries and joint ventures in the Czech Republic, compared to a control group of German firms without FDI in this host country.The impact of firm and industry characteristics on FDI decisions is assessed by estimating two-step Heckman models.We find that larger,more productive and more experienced firms are more likely to invest in the Czech Republic. Firm characteristics also affect the size of FDI.However, the relevance of firm and industry characteristics differs between the manufacturing and services sectors and depends on whether FDI is horizontal or vertical.
Keywords: F23; L25; 330